(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2021)
This article discusses the verdict of the Indira Gandhi case at the Federal Court and the jurisdictional conflict vis-à-vis Civil and Sharia Courts in matters pertaining to the dissolution of marriage in Section 51 of Act 164 and the determination of the religion of a child. This article aims to find a solution in the event of legal disputes between the aforementioned courts. The methods used in this study are library research and comparative analysis. Comparisons between the Subashini, Fatimah Tan and Nyonya Tahir cases are made, as well as comparisons regarding the definition of the term "parent" in the Federal Constitution and the Act/Enactments of the Administration of Islamic Law. Recent developments of Section 51 of Act 164 are also discussed. The finding indicates that the word "parent" has various meanings. The outcome of this study suggests that this case might imply a "binding precedent" in determining the religion of a child in the future, thus putting the Sharia Court’s jurisdiction of judicial review in question. Keywords: Administration of Islamic Law, jurisdictional conflict, Ahmad Ibrahim, Section 51, Act 1964